2009
DOI: 10.1097/iae.0b013e31819a6154
|View full text |Cite
|
Sign up to set email alerts
|

First Versus Second Eye Intravitreal Ranibizumab Therapy for Wet Amd

Abstract: Second eye patients tend to present to clinical diagnosis at a better visual acuity than first ones and subsequently have better chances for better posttreatment visual acuity. However, both groups have an equal chance of significant visual improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
2
5
0
1
Order By: Relevance
“…The results of the influence of different clinical variables on VA values collected in this study are consistent with previous studies: patients >75 years have a more accelerated course of the neovascular process 21,22 ; VA changes over time are not influenced by gender differences 21,22 ; and the second eyes maintain a higher VA than the first eyes at all follow-up time points, although this is not significant 17,23,24 . Finally, we observed that, even with a higher initial VA in pseudophakic eyes, these experienced a more marked visual deterioration, three times greater compared to phakic eyes, despite the visual limitations secondary to the presence of an advanced cataract, typical of an aging population.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the influence of different clinical variables on VA values collected in this study are consistent with previous studies: patients >75 years have a more accelerated course of the neovascular process 21,22 ; VA changes over time are not influenced by gender differences 21,22 ; and the second eyes maintain a higher VA than the first eyes at all follow-up time points, although this is not significant 17,23,24 . Finally, we observed that, even with a higher initial VA in pseudophakic eyes, these experienced a more marked visual deterioration, three times greater compared to phakic eyes, despite the visual limitations secondary to the presence of an advanced cataract, typical of an aging population.…”
Section: Discussionsupporting
confidence: 91%
“…Drugs applied to the surface of the eye rarely penetrate the ocular surface or enter into the vitreous body and the retina ( Gaudana et al, 2010 ). Biological barriers such as the cornea, conjunctiva and the tear film limit penetration and bioavailability of topical drug preparations to the posterior segment of the eye and therefore direct injection of drugs to the vitreous is commonly used to target drugs to the retina ( Ayalasomayajula and Kompella, 2005; Carneiro et al, 2009; Eldaly and Styles, 2009; Yasukawa et al, 2001 ) but has the risk of significant complications including cataracts, vitreous haemorrhages and retinal detachment. There are several colloidal drug delivery systems such as liposomes ( Hathout et al, 2007; Kaur et al, 2004; Law et al, 2000 ), niosomes ( Abdelbary and El-Gendy, 2008 ), nanoparticles ( Agnihotri and Vavia, 2009 ) and nanoemulsions ( Badawi et al, 2008 ) that enhance bioavailability of drugs to the retina after eye drop administration.…”
Section: Discussionmentioning
confidence: 99%
“…The granular hypoautofluorescence may be a precursor of confluent hypoautofluorescence and a predictive sign of future loss of visual function, although further prospective studies are needed with larger sample size and longer follow-up in the future. Although contrast sensitivity improves from baseline with anti-VEGF therapy, [26][27][28][29][30][31] there is no published information concerning the correlations between SD-OCT or measures of RPE health such as autofluorescence imaging and contrast sensitivity in treated patients. Keane et al 32 using time domain OCT found a correlation between subretinal tissue thickness, subretinal tissue volume, and subretinal fluid volume with decreased contrast sensitivity.…”
Section: Discussionmentioning
confidence: 99%